Giant gastric lipoma presenting with melaena: A case report and review of the literature (Indian Journal of Case Reports, 2020)
Gastric lipomas are rare tumors of the gastrointestinal tract. The majority of the tumors are asymptomatic and detected incidentally. However, large tumors can present either bleeding or gastric outlet obstruction. Here, we present a case of giant gastric lipoma in the pyloric antrum presenting with melaena and treated by surgical resection. An elderly male presented to the emergency department with a history of abdominal pain and melanotic stools. Computed tomography (CT) showed a homogeneous submucosal mass of fat attenuation in the gastric antrum with ulceration subsequently confirmed on endoscopy. The patient underwent surgical resection of the tumor with distal gastrectomy. Pathologic examination showed a well-circumscribed, encapsulated mass comprised mature adipose tissue without atypia or mitotic figures, consistent with lipoma. This case highlights the importance of CT in not only predicting the accurate diagnosis of these masses but also to provide additional details such as sarcomatous changes and perigastric spread before endoscopy or surgery.